The Effect of Substrate Pre-treatment on Hydroxy-apatite Coated Titanium Alloy by High-velocity Oxy-fuel Process - Raden Dadan Ramdan; Budi Prawara; Rochim Suratman; Ferdian Marta; Ali Rinaldi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2017)
In order to fully meet bio-compatibility requirement of titanium alloy as implant material, coating with hydroxyapatite (HA) is normally applied. The present research concerns on the effect of substrate pre-treatment on the coating of HA on titanium alloy by high-velocity oxy fuel process (HVOF). Before the coating, all samples were pre-treated by thermo-mechanical treatment in order to obtain fine grain structure. Three type of substrate pre-treatment is then applied on different substrates, including, sand-blasting, sand-blasting+etching, and sand-blasting+etching+CNT intermediate layer. After coating, post-annealing treatment was applied on each sample and characterization was performed on the sample after the treatment. It was obtained that the sand-blasted sample has relatively rougher surface (SEM observation), lower degree of crystallinity (XRD characterization) and higher residual strain (XRD data calculation by Mud Master software) as compared with other samples. From FTIR characterization it can be obtained that all samples show no differences in orbital function.